1998
DOI: 10.1063/1.869805
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional blade–vortex interaction in the strong vortex regime

Abstract: A study of three-dimensional interaction between a blade and an initially columnar vortex was performed using flow visualization experiments and computer simulations for problems where the blade is translated normal to and impacts upon the vortex core. The reported research focuses on cases where the vortex is sufficiently strong that the blade boundary layer separates before the blade penetrates into the vortex core. The study examines the topology and evolution of the separated secondary vorticity from the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…In the orthogonal blade-vortex interaction and the cylinder-vortex interaction it was commonly observed that the translating vortex was influenced by the wall at some distance before the impact (Krishnamoorthy and Marshall 1998;Krishnamoorthy et al 1999). The cause was the boundary layer separation and ejection of secondary vortices from the body leading surface.…”
Section: Secondary Vorticity Ejection and Vortex Breakdownmentioning
confidence: 98%
“…In the orthogonal blade-vortex interaction and the cylinder-vortex interaction it was commonly observed that the translating vortex was influenced by the wall at some distance before the impact (Krishnamoorthy and Marshall 1998;Krishnamoorthy et al 1999). The cause was the boundary layer separation and ejection of secondary vortices from the body leading surface.…”
Section: Secondary Vorticity Ejection and Vortex Breakdownmentioning
confidence: 98%
“…The flattening out of the lift force prediction for I = 1.4 is similar to the effect of the steady-state lift force as observed in figure 4(b), whereas the transient lift force seems to dominate for the other cases plotted in figure 14(b). We also note that cases with small values of the impact parameter can exhibit shedding of vorticity from the blade boundary layer prior to impact of the vortex onto the blade surface (Krishnamoorthy & Marshall 1998), which imposes a lower limit of approximately unity on the value of I, below which the vortex-blade interaction problem is fundamentally altered.…”
Section: Vortex Cutting With Axial Flowmentioning
confidence: 99%
“…As the ejected vortex loops wrap around the columnar vortex, they are gradually entrained into the vortex core due to their self-induced velocity. A computational study of the response of a columnar vortex to a wrapped vortex loop is given by Krishnamoorthy and Marshall [8]. This study examined the process by which azimuthal vorticity is generated within the columnar vortex through a combination of radial tilting of the vortex lines by the flow induced by the vortex loop, followed by azimuthal tilting of the vortex lines due to the radial variation of the azimuthal velocity of the columnar vortex.…”
Section: Strong-vortex Regimementioning
confidence: 99%
“…The series of experiments conducted at Iowa by Krishnamoorthy and Marshall [8,49,50] particularly examine the effect of the impact parameter on OBVI for a subcritical vortex. The experiments were performed by forming an intake vortex in a cylindrical tank, with tangential jets at the tank top and an orifice through which liquid was removed at the bottom (Fig.…”
Section: Experimental Studies At the University Of Iowamentioning
confidence: 99%
See 1 more Smart Citation